Tribological evaluation of a novel scallop-shell CaCO3 additive for extracted banana peel oil lubricant - Abdullah, Muhammad Ilman Hakimi Chua; Abdollah, Mohd Fadzli; Mohamad Fazdhli, Fawzan Hanafi; Jie, Chye Wong; Khashi’ie, Najiyah Safwa; Sundi @ Suandi, Syahrul Azwan; Waini, Iskandar; Mohamad, Effendi; Abdullah, Rohana; Puspitasari, Poppy; Avita, Ayu (Malaysian Tribology Society (Mytribos), 2024)
Nowadays, many sectors use lubrication derived from petroleum oil, resulting in severe environmental pollution. Hence, as a countermeasure, developing lubricants from organic sources is gaining attention. This research aimed to formulate a new bio-based banana peel oil by adding scallop shell nanoparticles (SSNs) as an additive. The process involved extracting banana peel oil (BPO) using a Szf-06A Soxhlet extraction fat analyser. The extracted oil was mixed with 0.5 vol% of three types of SSNs as an additive, and the mixture was then homogenised using ultrasonication. A tribological test using a four-ball tester, according to ASTM D-4172, was performed to determine the coefficient of friction (CoF) and the wear scar diameter (WSD). Scanning electron microscopy (SEM) was conducted to verify the wear mechanism. Samples with commercial-sized SSN additives yielded the best CoF (0.08385) and WSD (0.67 mm) results, indicating that commercial SSN additives can improve the physical properties and enhance the excellent anti-wear and anti-friction characteristics of lubricant mixtures compared to mineral oil.